Successful Clinical Remission of Perianal Extramammary Paget Disease with Intralesional IL-2 and Topical Imiquimod Treatment: A Case Report - E, Savonitto; C, Giacomantonio; L, Helyer (Archives of Clinical and Medical Case Reports, 2022)
Extramammary Paget disease is a rare intraepithelial adenocarcinoma that affects mainly in the perianal, genital and axillary regions. While wide local excision remains the gold-standard, not all patients are candidates for extensive surgical management due to metastases, poor baseline function, and patient preference. Herein, we present a case of successful clinical remission in a 63-year-old male with a perianal extramammary Paget disease.